1989
DOI: 10.1021/jf00086a025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prefrying times on the nutritive value of canned tilapia meat

Abstract: Tilapia meat was placed in the fryer filled with frying oil preheated to 180 OC. The frying times were 2, 5,10, 15, or 20 min. The fried meat was then packed in 209 X 409 cans, hermetically sealed, and retorted. As the frying time increased beyond 10 min, available lysine and in vitro protein digestibility of the meat decreased significantly (P < 0.05) in fried tilapia meat. Rats on diets of tilapia meat fried for 15 or 20 min containing 10% protein had poor growth and lower net protein utilization (NPU) (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…, 1994; Garcia‐Arias et al. , 2003), and the frying duration (Shiau & Shue, 1989; Hoffman et al. , 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1994; Garcia‐Arias et al. , 2003), and the frying duration (Shiau & Shue, 1989; Hoffman et al. , 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers found higher lipid contents in fried fish fillet than those in raw or other cooked fish fillets as a consequence of the absorption of the oil by the fillets (Mustafa & Medeiros, 1985;Steiner-Asiedu et al, 1991;Gokoglu et al, 2004). In addition, it was reported that the amount of lipid in the fried fish, which was expressed on a dry-weight basis, could change depending on the initial lipid content of the fish (Mai et al, 1978;Gall et al, 1983;Hoffman et al, 1994;Garcia-Arias et al, 2003), and the frying duration (Shiau & Shue, 1989;Hoffman et al, 1994). In the present study, the lipid contents of the fried fish samples were found to be higher than the fresh ones.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…In many tropical and subtropical countries, fresh tilapia is becoming a popular substitute for quality animal protein source for human consumption, due to its fast growing, resistant to disease and handling, reproduction in captivity, efficient conversion of low‐protein diets, and for being able to tolerate a wide range of environmental conditions (Shiau and Shue 1989). The global production has been greatly influenced by a rapid expansion of Nile tilapia ( Oreochromis niloticus ) and Mossambique tilapia ( Oreochromis mossabicus ) culture in many reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature in India on thermal processing of tilapia is very meager. Shiau and Shue (1989) studied the effects of prefrying times on the nutritive value of canned tilapia meat. However, market for processed foods has been growing at a greater rate due to changes in life style and food habits of the people.…”
Section: Introductionmentioning
confidence: 99%
“…That could be an explanation for the significant decrease in proteins and the relative increase in carbohydrates. Other authors found total nitrogen and protein decrease in other fried foods (Ponnampalam and Mondy, 1983;Shiau and Shue, 1989). Significant differences between RS and SFF3 were not detected in ash content.…”
Section: Proximate Composition On Raw Soybean and Fried-salted Soybeanmentioning
confidence: 87%